Efficacy and Safety of Dapagliflozin in Heart Failure With Reduced Ejection Fraction According to Age: Insights From DAPA-HF. Issue 2 (14th January 2020) - Martinez, Felipe A.; Serenelli, Matteo; Nicolau, Jose C.; Petrie, Mark C.; Chiang, Chern-En; Tereshchenko, Sergey; Solomon, Scott D.; Inzucchi, Silvio E.; Køber, Lars; Kosiborod, Mikhail N.; Ponikowski, Piotr; Sabatine, Marc S.; et al.
Abstract : Background: The DAPA-HF trial (Dapagliflozin and Prevention of Adverse-Outcomes in Heart Failure) showed that dapagliflozin added to other guideline-recommended therapies reduced the risk of mortality and heart failure hospitalization and improved symptoms in patients with heart failure and reduced ejection fraction. We examined the effects of dapagliflozin according to age, given potential concerns about the efficacy and safety of therapies in the elderly. Methods: Patients in New York Heart Association functional class II or greater with a left ventricular ejection fraction ⩽40% and a modest elevation of NT-proBNP (N-terminal pro-B-type natriuretic peptide) were eligible. Key exclusion criteria included systolic blood pressure <95 mm Hg and estimated glomerular filtration rate <30 mL·min −1 ·1.73 m −2 . The primary outcome was the composite of an episode of worsening heart failure (heart failure hospitalization or urgent heart failure visit) or cardiovascular death, whichever occurred first. Results: A total of 4744 patients 22 to 94 years of age (mean age, 66.3 [SD 10.9] years) were randomized: 636 patients (13.4%) were <55 years of age, 1242 (26.2%) were 55 to 64 years of age, 1717 (36.2%) were 65 to 74 years of age, and 1149 (24.2%) were ≥75 years of age. The rate of the primary outcome (per 100 person-years, placebo arm) in each age group was 13.6 (95% CI, 10.4–17.9), 15.7 (95% CI, 13.2–18.7), 15.1 (95% CI, 13.1–17.5), and 18.0 (95% CI, 15.2–21.4) with corresponding dapagliflozin/placebo hazard ratios of 0.87 (95% CI, 0.60–1.28), 0.71 (95% CI, 0.55–0.93), 0.76 (95% CI, 0.61–0.95), and 0.68 (95% CI, 0.53–0.88; P for interaction=0.76). Consistent benefits were observed for the components of the primary outcome, all-cause mortality, and symptoms. Although adverse events and study drug discontinuation increased with age, neither was significantly more common with dapagliflozin in any age group. Conclusions: Dapagliflozin reduced the risk of death and worsening heart failure and improved symptoms across the broad spectrum of age studied in DAPA-HF. There was no significant imbalance in tolerability or safety events between dapagliflozin and placebo, even in elderly individuals. Clinical Trial Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03036124. Abstract : Supplemental Digital Content is available in the text.